2022
DOI: 10.1186/s12935-022-02616-9
|View full text |Cite
|
Sign up to set email alerts
|

YOD1 serves as a potential prognostic biomarker for pancreatic cancer

Abstract: Background Ubiquitination is a basic post-translational modification of intracellular proteins and can be reversed enzymatically by DUBs (deubiquitinating enzymes). More than 90 DUBs have been identified. Among them, the deubiquitinating enzyme YOD1, a member of the ovarian tumor domain protease (OTUs) subfamily, is involved in the regulation of endoplasmic reticulum (ER)-related degradation pathways. In fact, it is reported that YOD1 is an important proliferation and metastasis-inducing gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Differently, we found that YOD1 showed a strong correlation with poor prognosis in TNBC patients. Previous studies have reported the regulatory role of YOD1 in cancer developments, such as, YOD1 suppresses the malignant development of ovarian cancer via binding to miR-4429 [ 42 ] and YOD1 serves as a potential prognostic biomarker for pancreatic cancer through cell adhesion molecules, p53, Hippo, TGF-β and other pathways [ 43 ]. However, no study has reported the effect and mechanism of YOD1 on the development of TNBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently, we found that YOD1 showed a strong correlation with poor prognosis in TNBC patients. Previous studies have reported the regulatory role of YOD1 in cancer developments, such as, YOD1 suppresses the malignant development of ovarian cancer via binding to miR-4429 [ 42 ] and YOD1 serves as a potential prognostic biomarker for pancreatic cancer through cell adhesion molecules, p53, Hippo, TGF-β and other pathways [ 43 ]. However, no study has reported the effect and mechanism of YOD1 on the development of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…YOD1 is a member of the deubiquitinating enzyme family, whose protein comprises three conserved domains: N-terminal UBX domain, central otubain domain and C-terminal C2H2-type Znf domain [ 24 , 33 ]. Some studies have reported that protein domains, accessories to the catalytic core, are required for YOD1 function [ 19 , 33 , 43 ]. YOD1 is associated with p97 to facilitate protein dislocation, in which the dominant negative effect is dependent on the UBX and Zinc finger domains, appended to the N- and C-terminus of the catalytic otubain core domain, respectively [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, extensive research has been performed on YOD1 regulation using different miRNAs. Several studies have reported correlations between YOD1 expression and various cancers including pancreatic and ovarian cancers 258,259 . In addition to YOD1, ATAXIN‐3 represents a major mammalian DUB.…”
Section: Human Phenotypes and Animal And Cellular Disease Models Asso...mentioning
confidence: 99%
“…Ubqln2 À/À mice 288 Ubqln2 À/À rats 289 Adult Ubqln2 deficient mice developed hyperactivity HeLa cells 288,290 NSC34 mouse motor neuron cells 288 HEK293 cells 291 Ubiquilin 3 -Ubqln3 298 cancers including pancreatic and ovarian cancers. 258,259 In addition to YOD1, ATAXIN-3 represents a major mammalian DUB. It has also been shown to interact with p97.…”
Section: Hek293 Cells 280mentioning
confidence: 99%
“…In addition, YOD1 deubiquitinase is highly expressed in PDAC and accelerates tumor metastasis, although the underlying mechanism remains unclear ( Zhang et al, 2022 ). It is noticeable that USP9X is reported inactivated in more than 50% of PDAC, and its level is inversely associated with metastatic burden in advanced disease, which may result in anoikis ( Perez-Mancera et al, 2012 ) and inhibition of programmed cell death ( Taddei et al, 2012 ).…”
Section: How E3s and Dubs Influence Various Phenotypes Of Pdacmentioning
confidence: 99%